Analisis Daya Dukung Tanah dengan Plate Loading Test untuk Perencanaan Fondasi Dangkal (Studi Kasus: Kota Medan) - Miguel Felix Wijaya; Debora Lau; Alfadhella Ridwan (Universitas Muhammadiyah Surabaya, 2026)
Shallow foundation planning requires accurate estimation of soil bearing capacity to ensure the safety, stability, and efficiency of building structures. This study aims to analyze the soil bearing capacity based on Plate Loading Test (PLT) results for the shallow foundation design of a storage warehouse in the Medan area, North Sumatra. PLT testing was conducted at two test points representing the soil conditions at the research location, following ASTM D 1194-94 and ASTM D1196/D1196M standards. The parameters analyzed include the load-settlement curve, ultimate bearing capacity, soil reaction modulus (k), and estimated California Bearing Ratio (CBR) values. The results show that the ultimate soil bearing capacity ranges from 570–690 kN/m² with relatively small plate settlements of 4.8–7.2 mm, indicating stable soil behavior. The soil reaction modulus values were obtained in the range of 22,800–27,600 kN/m³, while the estimated CBR values ranged from 26–27.69%. Overall, these results indicate that the soil at the research location has good bearing capacity and falls into the category of high-density soil. Therefore, the soil conditions are declared suitable for use as a supporting layer for shallow foundations in industrial buildings.